Socio-spatial differences in older urban residents’ engagement against transportation noise? Implications for distributional and procedural justice in noise action planning - Riedel, Natalie; Brunswieck, Ramona; Hartig, Christina; Moebus, Susanne; Jöckel, Karl-Heinz; Bolte, Gabriele (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Exposure to transportation noise is a highly prevalent health burden in urban areas. Social-spatially unequal distributions of transportation noise exposure can contribute to health inequalities (distributional environmental justice). Noise action planning according to the EU Environmental Noise Directive is the instrument for noise abatement at the local level. In this context, public participation in terms of procedural environmental justice becomes relevant. Socio-spatial indicators used to describe environmental justice mainly deal with the distributional aspect. The question is to what extent both unequal environmental quality on the one hand and unequal participation on the other can be traced by indicators and spatial units typically used in social monitoring at the local level. Using the distance measure index of German social welfare rates and the local voter turnout in 2014, the socio-spatial distribution of factors of objective environmental quality, subjective noise exposure and engagement against transportation noise among older residents in three major cities in the German Ruhr region was examined. In order to address the observed inequalities within noise action planning, distributional and procedural aspects have to be integrated in noise action planning.
Keywords: Transportation noise; Procedural environmental justice; Participation; Noise action planning; Indicators